Low-methane yield sheep have smaller rumens and shorter rumen retention time. Issue 4 (8th October 2013) - Goopy, John P.; Donaldson, Alastair; Hegarty, Roger; Vercoe, Philip E.; Haynes, Fay; Barnett, Mark; Oddy, V. Hutton
Abstract : In the present study, following the measurement of methane emissions from 160 mature ewes three times, a subset of twenty ewes was selected for further emission and physiological studies. Ewes were selected on the basis of methane yield (MY; g CH4 /kg DM intake) being low (Low MY: >1sd below the mean; n 10) or high (High MY: >1sd above the mean; n 10) when fed a blended chaff ration at a fixed feeding level (1·2-fold maintenance energy requirements). The difference between the Low- and High-MY groups observed at the time of selection was maintained ( P = 0·001) when remeasured 1–7 months later during digesta kinetics studies. Low MY was associated with a shorter mean retention time of particulate ( P < 0·01) and liquid ( P < 0·001) digesta, less amounts of rumen particulate contents ( P < 0·01) and a smaller rumen volume ( P < 0·05), but not apparent DM digestibility ( P = 0·27) or urinary allantoin excretion ( P = 0·89). Computer tomography scanning of the sheep's rumens after an overnight fast revealed a trend towards the Low-MY sheep having more clearly demarcated rumen gas and liquid phases ( P = 0·10). These findings indicate that the selection of ruminants for low MY may have important consequences for an animal's nutritional physiology.